2022
DOI: 10.1038/s41467-022-30624-w
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell chromatin profiling of the primitive gut tube reveals regulatory dynamics underlying lineage fate decisions

Abstract: Development of the gastrointestinal system occurs after gut tube closure, guided by spatial and temporal control of gene expression. However, it remains unclear what forces regulate these spatiotemporal gene expression patterns. Here we perform single-cell chromatin profiling of the primitive gut tube to reveal organ-specific chromatin patterns that reflect the anatomical patterns of distinct organs. We generate a comprehensive map of epigenomic changes throughout gut development, demonstrating that dynamic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Due to the scarcity of cleavage events in an individual cell, most chromatin accessibility regions in a single cell have only one aligned fragment, making the potential influence of intrinsic cleavage biases more substantial in scATAC-seq data than in bulk ATAC-seq data. We collected scATAC-seq datasets generated using different platforms for different biological samples, human hematopoietic cells 37 , mixed human cell lines 21 , and mouse primitive gut tube 38 , and found that the scATAC-seq data contained similar intrinsic cleavage biases to bulk data with highly correlated bias scores estimated by SELMA (Supplementary Fig. 9a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the scarcity of cleavage events in an individual cell, most chromatin accessibility regions in a single cell have only one aligned fragment, making the potential influence of intrinsic cleavage biases more substantial in scATAC-seq data than in bulk ATAC-seq data. We collected scATAC-seq datasets generated using different platforms for different biological samples, human hematopoietic cells 37 , mixed human cell lines 21 , and mouse primitive gut tube 38 , and found that the scATAC-seq data contained similar intrinsic cleavage biases to bulk data with highly correlated bias scores estimated by SELMA (Supplementary Fig. 9a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the scarcity of cleavage events in an individual cell, most chromatin accessibility regions in a single cell have only one aligned fragment, making the potential influence of intrinsic cleavage biases more substantial in scATAC-seq data than in bulk ATAC-seq data. We collected scATAC-seq datasets generated using different platforms for different biological samples, human hematopoietic cells 37 , human cell lines 21 , and mouse primitive gut tube 38 , and found that the scATAC-seq data contained similar intrinsic cleavage biases to bulk data with highly correlated bias scores estimated by SELMA (Fig. S9a-c).…”
Section: Resultsmentioning
confidence: 99%
“…S13a). It is known that the gut endoderm has a spatial pattern along the anterior-posterior axis at ~E7.5 and will form seven organs, including thyroid, thymus, lung, liver, pancreas, small intestine and colon, at ~E9.0 48,49 . Accordingly, it is expected that the gut endoderm cells of the two embryos are undergoing incipient fate commitments.…”
Section: Tca Reveals Incipient Cell Fate Commitments By Identifying L...mentioning
confidence: 99%